Pengaruh Pendampingan Terhadap Penurunan Kadar Glukosa Darah Pasien Diabetes Mellitus Didesa Bangun Rejo Tahun 2024 - Erika Erika; Indra Agussamad; Eko Murdianto; Yuniata Yuniata (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Type II Diabetes Mellitus accounts for about 90-95% of all diabetes cases in the world. Education is the main basis for effective treatment and prevention of Diabetes Mellitus. The mentoring method is considered more effective than conventional counseling. This study aims to determine the effect of mentoring on knowledge, dietary adherence, medication adherence, physical activity, and blood glucose levels of Diabetic Mellitus patients in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency. This study is a purely experimental study with random grouping of samples and assessments carried out before and after the intervention. The research was conducted in Bangun Rejo Village from March to June 2024. The results showed a significant difference in the knowledge of Diabetes Mellitus patients before and after the assistance with a p-value < 0.05. In addition, there was an effect of assistance on dietary adherence and a decrease in blood glucose levels in patients with Diabetes Mellitus with a p-value of < 0.05. This finding is expected to be an information material for health agencies, especially Bangun Rejo Village, to improve services to people with Diabetes Mmelitus and provide input for the Tanjung Morawa District Government, Deli Serdang Regency, especially the Health Office, in developing an educational intervention program with a mentoring approach to achieve optimal metabolic control.